Treatment of peripheral extremity pain with TENS: A report of three cases - Thiel, Haymo W (1987)
This paper reviews three cases in which radiculopathies of the cervical and lumbar spine were successfully managed by the use of transcutaneous electrical nerve stimulation (TENS) in addition to, or instead of, spinal manipulative therapy. Characteristics of TENS, indications for its use, and application procedures are discussed.